The Dramatic Transformation Between Seriousness and Humor in Ahmad Matar's Poems - Ibrahim, Zana Muhammad (Journal of Tikrit University for Humanities, 2023)
The focus of our research is to the genre of dramatic poetry, namely the form known as poetic drama, as shown by the modern Arabic poetry, with particular emphasis on the works of Ahmad Matar. The framework of poetic rhythm was only presented in a novel way. The aforementioned metamorphosis had an impact on several aspects, including poetic consciousness, the configuration of the artistic representation, the language framework, and the creative composition. This alteration occurred during the shift from a purely lyrical format to a lyrical-dramatic format.This study focuses on a significant shift in the Arabic poem, specifically the transformation from a dramatic form to a more democratic one. The importance of this study lies in its examination of Ahmed Matar's poetry, which reflects his personal experiences and the evolving societal context. Additionally, it aims to observe the rapid changes occurring in Arab and Iraqi society. Particularly noteworthy is his critique of these transitions, as well as his use of literary devices, including irony and antagonistic dichotomies, in a captivating manner. By using elements of both seriousness and humour, the author effectively engages the reader.It is essential for each research to establish a robust theoretical framework as its basis, and to adopt a coherent methodology to guide its progression. This study used a psychological framework to examine the influence of stable personality characteristics on an individual's behaviour. These qualities are manifested via consistent emotional and expressive patterns shown by the individual.The present research has an introductory section followed by two main sections. In the introductory section, an exploration was conducted on the notion of seriousness and humour within language, as well as its interconnectedness with societal aspects. Regarding the first axis, I examined the themes of gravity and steadfastness in Ahmad Matar's poetry, as well as his adeptness in transitioning to the realm of humour. Specifically, I explored the use of sarcasm, which conveys a meaning contrary to its outer appearance. The use of sarcasm might manifest itself via the first expression of admiration or in the form of a typical exchange, however it conceals within it a layer of acerbic censure. Ultimately, the conclusions of my investigation were documented by me.